Pengaruh Lingkungan Kerja Dan Pengembangan Karier Terhadap Kinerja Pegawai Pada Satuan Polisi Pamong Praja Kabupaten Karawang - Yunia Halifasya; Danny Ramdani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research aims to determine the effect of the work environment and career development on employee performance on Satpol PP Kabupaten Karawang. The research method is a quantitative research with descriptive and verification approach. The study uses primary data, obtained from questionnaires which is distributed to the respondents. The sample in this study are employee of Satpol PP Kabupaten Karawang. This study uses the slovin formula with an error rate of 5% in the sample calculation and is determined by using probability sampling technique. The analysis of this study uses multiple regression analysis with helping of SPSS 26 software tools. The result of this study indicate that there is a simultaneous positive significant effect between the work environment and career development on performance of 45.5%.